Retention strategies : the key to attracting and retaining excellent employees - Bussin, Mark (Talent management series, 2019)
In the current economic environment, retention is one of the foremost concerns of all organisations. Leading organisations are citing retention as a key challenge and central objective; and no organisation can expect to survive if its retention game is not on point. A sound retention strategy results in lower staff turnover rates, which means: Reduced costs to the company, higher revenues and profitability, more productive staff and increased work morale. Retention is, in fact, a win-win deal for both parties - the employer and the employee. Retention Strategies is a complete how-to book to help you implement a sound retention strategy for today's workplace.